Determinants of the Human Development Index in Indonesia in the Perspective of Maqasid al-Shariah - Hafidza Sanshia Arum; Tasriani; Miftah, Desrir (Jurnal Ar-Ribh, 2026)
This study analyzes the determinants of the Human Development Index in Indonesia by examining the role of GDP per capita, economic growth, and income inequality in the perspective of maqasid al-shariah. This research is motivated by the phenomenon that high economic growth is not always followed by an improvement in the quality of human development. The research uses a quantitative approach with panel data from 34 provinces in Indonesia for the 2020–2024 period sourced from the Central Statistics Agency. The analysis was carried out using panel data regression with a Fixed Effect Model and robust standard error. The results of the study show that GDP per capita has a positive and significant effect on the Human Development Index. Meanwhile, economic growth and income inequality did not have a significant effect partially. However, simultaneously the three variables have a significant effect on human development. These findings show that human development is more influenced by the average economic capacity of a community than aggregate economic growth or income distribution in the short term. In the perspective of maqasid al-shariah, these results affirm the importance of a balance between economic growth, social justice, and community welfare. This research contributes by integrating economic empirical analysis with the perspective of maqasid al-shariah as a more comprehensive framework in understanding human development.